On the undisclosed transfer of abusive Catholic priests: A field theoretical analysis of the sexual repression within the Catholic Church and the use of legitimate language - Armbruster, André (Critical research on religion, 2022)
Catholic priests who sexually abused minors were transferred to other parishes without disclosing the actual reason for their transfer. Based on reports from Ireland, Germany, and the USA, and relying on Bourdieu’s concepts of field and habitus, this article demonstrates that first, the practices of denying and withholding information even to fellow priests are consequences of the repression of sexuality within the Catholic Church. The Church has not provided a legitimate language for priests to be able to engage openly about sexuality. Sexual repression as a field structure is incorporated into the priests’ habitus, resulting in self-censorship when it comes to articulating the issue of sexual abuse. Secondly, the article accounts for the change within the Catholic field and the priest’s habitus, which has resulted in the facility to verbally express sexual matters in order that the undisclosed practice of transferring abusive priests finally stopped.